Perspectives on current models of Friedreich’s ataxia - Kelekçi, Simge; Yıldız, Abdullah Burak; Sevinç, Kenan; Çimen, Deniz Uğurlu; Önder, Tamer (Frontiers in Cell and Developmental Biology, 2022)
Friedreich’s ataxia (FRDA, OMIM#229300) is the most common hereditary ataxia, resulting from the reduction of frataxin protein levels due to the expansion of GAA repeats in the first intron of the FXN gene. Why the triplet repeat expansion causes a decrease in Frataxin protein levels is not entirely known. Generation of effective FRDA disease models is crucial for answering questions regarding the pathophysiology of this disease. There have been considerable efforts to generate in vitro and in vivo models of FRDA. In this perspective article, we highlight studies conducted using FRDA animal models, patient-derived materials, and particularly induced pluripotent stem cell (iPSC)-derived models. We discuss the current challenges in using FRDA animal models and patient-derived cells. Additionally, we provide a brief overview of how iPSC-based models of FRDA were used to investigate the main pathways involved in disease progression and to screen for potential therapeutic agents for FRDA. The specific focus of this perspective article is to discuss the outlook and the remaining challenges in the context of FRDA iPSC-based models.